Asal-usul elite Minangkabau modern : respons terhadap kolonial Belanda abad xix/xx / Elizabeth E. Graves ; penerjemah, Novi Andri, Leni Marlina, Nurasni ; editor, Mustika Zed - GRAVES, Elizabeth E.; Novi Andri; Leni Marlina; Nurasni; Mestika Zed (Yayasan Obor Indonesia, 2007)
xvi, 309 hlm. : ilus. ; 21 cm [3 eks.]